Notas sobre a expansão do agronegócio: das regularidades discursivas aos homens de camisa azul - Meyer, Gustavo (2022)
This article reflects on the intertwining between discourses and images that support the expansion and embeddedness of the so-called "agribusiness society". Although its operation implies the imposition of interests, manipulated by those who occupy a privileged position, the discursiveness that sustains their practices is inserted in the border of the field of culture. Through an ethnography directed to social groups that inhabit such a society in a portion of the Brazilian Central Plateau, we describe how these groups, triggering a kind of prototype (the "blue-collar man"), share an ethos, values, beliefs and traits that forge a collectivity and an identity.